The contribution of infrared thermography in the characterization of jute based composites. (15th April 2018) - Boccardi, Simone; Carlomagno, Giovanni Maria; Meola, Carosena; Russo, Pietro; Simeoli, Giorgio
Abstract: The growing environmental awareness is driving attention towards the development of ever more ecological and friendly materials, calling for the use of natural matrix and fibres in composite materials. The attention of this work is focused on two types of composites, which both include jute as reinforcement but different matrices. One matrix is polypropylene (PP) and the other one is poly-lactic acid (PLA), so to have partial, or total, natural materials. Several specimens are prepared and tested under impact, or cyclic and quasi-static bending. An infrared imaging device is used to in-line monitoring of specimens under each test. The visualization of thermal effects coupled with mechanical stresses allows getting complimentary information, which may be exploited to better understand the reaction of materials to applied forces and their damaging modes.